Functionality Performance of Information Systems in Higher Education Institutions - Rodolfo, Jr. Flordeliza Dollado (Universitas Bina Darma, 2022)
The goal of this research was to evaluate the performance of information systems in terms of functionality of the in-house developed and outsourced information systems of Higher Education Institutions (HEIs) in Samar, Philippines. A descriptive research design was used in order to obtain information on the performance of the information systems in terms of functionality. The technique employed for data collection was physical evaluation using an observation sheet. A total of thirteen (13) information systems were subjected to performance evaluation as there were thirteen HEIs from the different provinces of Samar Island that participated in the study. The overall results showed that the outsourced systems had better performance in terms of functionality since most of the indicators were completely existing and functional. On the other hand, the in-house systems have performed fairly with regards to the required features and functionalities of the system. The results of the study suggest that HEIs should acquire information systems that are completely functional, regardless of what acquisition method is adopted. Having information systems equipped with the required functionality features, the administrative and academic functions of HEIs are effectively and efficiently delivered.